Successful laparoscopic repair of an incarcerated Bochdalek hernia associated with increased intra-abdominal pressure during use of blow gun: A case report. (2016) - Harada, Manabu; Tsujimoto, Hironori; Nagata, Ken; Ito, Nozomi; Yamazaki, Kenji; Kanematsu, Kyohei; Horiguchi, Hiroyuki; Kajiwara, Yoshiki; Hiraki, Shuichi; Aosasa, Suefumi; Yamamoto, Junji; Hase, Kazuo
Highlights: Bochdalek hernia is a congenital diaphragmatic hernia. An incarcerated Bochdalek hernias is an uncommon in an adult. Laparoscopic repair of an incarcerated Bochdalek hernia is safe and feasible. Abstract: Background: Bochdalek hernia is a congenital diaphragmatic hernia, and adult cases are rare, with a reported frequency of 0.17%–6% among all diaphragmatic hernias. Presentation of case: A 78-year-old man was referred to our hospital with a sudden onset of whole abdominal pain after playing with a blow gun. Chest radiography and computed tomography revealed diaphragmatic hernia with the small intestine. We therefore diagnosed him with an incarcerated Bochdalek hernia associated with increased intra-abdominal pressure during use of blow gun. Laparoscopic repair was performed. The omentum, transverse colon, and small intestine were located in the left thoracic cavity, without ischemic change. After placing the herniated organs into the abdominal cavity, we performed a primary closure of the diaphragmatic defect with interrupted non-absorbable sutures. Discussion: It is generally recommended that all adult Bochdalek hernia patients undergo surgical repair to prevent life-threatening complications due to incarceration. Recently, laparoscopic techniques for repair the hernia have gained popularity, especially in elective cases. In our case, we could successfully perform emergency laparoscopic repair, as it is associated with a shorter inpatient hospitalization period. Conclusion: An incarcerated Bochdalek hernias associated with increased intra-abdominal pressure is an uncommon clinical finding in an adult, and laparoscopic repair of an incarcerated Bochdalek hernia is safe, feasible, and an excellent option as it is minimally invasive.